(untitled) - Mallik, A K (Oxford, U.K.)
Contents: Stability of static equailibrium; Basic dynamic considerations; Stability problems in dynamics; Emergence of length scale and pattern formation.
Keywords: Stability,Mechanics, applied,Nonlinear mechanics